Sebaran Partikel Tersuspensi, Partikel Terlarut dan Laju Sedimentasi di Teluk Kelabat Luar, Area Pengaruh Penambangan Timah - Indra Ambalika; Umroh; Mohammad Agung Nugraha; Aditya Pamungkas; Eva Utami; Irma Akhrianti; Mualimah Hudatwi; Suci Puspita Sari; Titin Marfuah (Scientific Timeline, 2021)
Water turbidity will impact how far the level of distribution of suspended and dissolved particles will affect the life of marine biota. This study aimed to determine the distribution of suspended and dissolved particles in the waters of Teluk Kelabat Luar. Water sampling was carried out in July 2019, representing the east monsoon. Determination of the water sampling location was by purposive sampling method, and then the data were analyzed descriptively. The results showed that the concentration of total suspended solids (TSS) on the surface (1 m) of Teluk Kelabat Luar has the highest concentration at point 4 (KL 4) with TSS concentrations in the range of 36,5 mg/L and point 14 (KL 14) in the range of 34,0 mg/L. Point 4 was the post-tin mining location. From this, it could be seen that the waters are still affected even after mining activities, namely the high concentration of TSS. The analysis of total dissolved solids (TDS) showed the highest concentration at point 12 (KL 12). The sedimentation rate in Teluk Kelabat Luar is in the medium-severe category, which is around 1,92 mL/hour. The results showed that mining had a tremendous effect on the level of suspended particles in the waters.